MUSICAL-RHYTHMIC INSTRUMENTATION IS THE BASIS FOR DEVELOPMENT OF EXECUTIVE SKILLS OF JUNIOR SCHOOLCHILDREN - Vovk, Myron; Dzon Juliіa (Mountain School of Ukrainian Carpaty, 2019)
In this article, the author raises the problem of using shock-rhythmic tools at music art lessons in elementary schools of general education. The results of experimental research and the study of advanced experience in the schools of the Baltic states convince in the importance of determining the place of collective music making in the system of music classes, creating the appropriate pedagogical and didactic conditions for the organization of the educational process, introducing a systematic approach (phase-phase sequence) to the development of musical and practical activity of junior pupils. Elementary music making provides the involvement in the practical music making of all the children at the lesson, even with partial disabilities of violations of auditory and vocal coordination, promotes awareness of schoolchildren of their forces, positively affects creativity, helps their aesthetic growth. An important factor in determining the conditions is the optimal combination of instrumentation with singing. It is the «foundation» of working with musical instruments should be a sonorous song melody. Such a condition ensures the structure of the lesson, complements and multiplies the types of children's musical creativity, forms their sense of executive autonomy, concentration and self-control. The development of didactic principles of the development of independent creative activity, the organization of the system of work with toolkits at the lesson, the substantiation of the pedagogical factors of the development of independence, –create an atmosphere of creativity and provide realization of compensation for children with insufficient vocal and singing ability. The use of musical instruments makes it possible for the teacher to engage all the children without any exception in the practical performance, notwithstanding the low level of vocal and auditory abilities of some separate class students. The use of rhythmic instrumentation should be implemented in the practice of educational classes at school, through continuous systematic work. Only then the learning process can become effective and bring the desired results.